2008
DOI: 10.1021/ol801550a
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile and Regiospecific Synthesis of Functionalized 1,3-Diarylisobenzofurans

Abstract: A convenient, versatile, and regiospecific synthesis of functionalized 1,3-diarylisobenzofurans has been developed. It involves chemoselective addition of arylmagnesium reagents to the aldehyde function of o-aroylbenzaldehydes, themselves readily obtained by lead tetraacetate oxidation of N-aroylhydrazones of salicylaldehydes. Various functional groups, including nitro, iodo, or ester functionalities, have thus been positioned with complete regiospecificity on the 1,3-diphenylisobenzofuran backbone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The mechanistic studies performed by Kotali and Katritzky showed that this rearrangement occurs through 1,3,4‐oxadiazoline and 1,3‐dioxane intermediates 7b. Einhorn et al8a and Dong et al8b also utilised this method for the synthesis of a range of o ‐diacylbenzenes. Although there are various reports on the formation of o ‐diacylbenzenes by LTA‐mediated oxidation, as mentioned above,7 so far this reaction has not been explored with heterocyclic aromatic compounds such as indoles, quinoline, and pyridines.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanistic studies performed by Kotali and Katritzky showed that this rearrangement occurs through 1,3,4‐oxadiazoline and 1,3‐dioxane intermediates 7b. Einhorn et al8a and Dong et al8b also utilised this method for the synthesis of a range of o ‐diacylbenzenes. Although there are various reports on the formation of o ‐diacylbenzenes by LTA‐mediated oxidation, as mentioned above,7 so far this reaction has not been explored with heterocyclic aromatic compounds such as indoles, quinoline, and pyridines.…”
Section: Introductionmentioning
confidence: 99%
“…A series of variously substituted diphenylisobenzofurans was synthesized by a previously described versatile method (16). The studied molecules are represented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The photochemical and photophysical properties of the IBFs are expected to be altered by the introduction of various substituents or functional groups at selected positions of the 1,3‐diarylisobenzofuran backbone. New versatile and regiospecific synthesis of functionalized IBF derivatives have been developed recently (15–17), giving a straightforward access to previously unknown compounds, and thus providing a library of diversely substituted IBFs. A thorough inspection of the events following the absorption of a photon is described hereafter.…”
Section: Introductionmentioning
confidence: 99%
“…Hexane and AcOEt for the chromatography were distilled before use. Cyclopropenes and 1,3‐diarylisobenzofurans were prepared following known procedures . Reactions were monitored by the TLC analysis using Silufol UV‐254 plates.…”
Section: Experimental Partmentioning
confidence: 99%